2017
DOI: 10.1148/radiol.2017162351
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ-weighted Dynamic Glucose-enhanced MR Imaging in the Human Brain

Abstract: Purpose To evaluate the ability to detect intracerebral regions of increased glucose concentration at T1ρ-weighted dynamic glucose-enhanced (DGE) magnetic resonance (MR) imaging at 7.0 T. Materials and Methods This prospective study was approved by the institutional review board. Nine patients with newly diagnosed glioblastoma and four healthy volunteers were included in this study from October 2015 to July 2016. Adiabatically prepared chemical exchange-sensitive spin-lock imaging was performed with a 7.0-T wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 27 publications
(12 reference statements)
6
120
0
1
Order By: Relevance
“…Because of the complicated pathology and limited number of cases studied in this initial pilot study, it is difficult to determine the exact pattern of enhancement with glucoCEST. Others also found that regions of DGE and Gd enhancement differed in area . In our previous 7T study, we noticed in 1 patient case that early enhancement corresponded to the Gd‐enhanced ring, whereas later enhancement spread through a larger tumor area not enhanced in the Gd T 1 ‐weighted scan.…”
Section: Discussionmentioning
confidence: 70%
“…Because of the complicated pathology and limited number of cases studied in this initial pilot study, it is difficult to determine the exact pattern of enhancement with glucoCEST. Others also found that regions of DGE and Gd enhancement differed in area . In our previous 7T study, we noticed in 1 patient case that early enhancement corresponded to the Gd‐enhanced ring, whereas later enhancement spread through a larger tumor area not enhanced in the Gd T 1 ‐weighted scan.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, two CESL‐based DGE contrast metrics were investigated. First, the R 1ρ ‐weighted dynamic glucose‐enhanced (DGE ρ ) contrast calculated according to Schuenke et al:DGEnormalρfalse(normaltfalse)=normalS50msfalse(reffalse)-S50ms(t)normalS50msfalse(reffalse)·50ms,with S 50ms (t) being the acquired R 1ρ ‐weighted images for the spin‐lock time (TSL) = 50 ms (i.e., TSL 1 ), and S 50ms (ref) being the average of the first 20 S 50ms (t) images. Note, in comparison to the original definition, DGE ρ in Equation is divided by the respective TSL = 50 ms to enable a direct comparison of contrast values (in units of Hz) to the second DGE contrast metric investigated in this study (Equation ).…”
Section: Methodsmentioning
confidence: 99%
“…Whether glucose in blood vessels, extracellular glucose, or intracellular phosphorylated glucose derivatives are the driving source for the observed DGE contrast remains to be investigated in depth . Furthermore, the applicability for examinations in humans has already been verified in independent pilot studies based on glucoCEST and glucoCESL . However, DGE contrast maps are prone to motion‐induced artifacts because DGE image series consist of data acquired before, during, and after glucose injection.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high‐resolution T 2 sequence imaging was performed at 7T MRI . CEST and T 2 image data were coregistered with the "Medical Imaging Interaction Toolkit" (MITK) software, using an automatic multimodal rigid registration algorithm …”
Section: Methodsmentioning
confidence: 99%